DEVELOPING TEACHING MATERIALS OF ISLAMIC EDUCATION AND ETHICS BASED ON THE VALUES OF LOCAL WISDOM - Usman Usman; Bahraeni Bahraeni; Sabaruddin Garancang (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2021)
Abstract:This study aims to describe the profile of developing Islamic education and character teaching materials based on the local wisdom values, as well as to implement the development of Islamic Education and Character teaching materials based on the local wisdom values that are legitimated, practical, and effective. This study used development research that refers to the theory of Thiagarajan and Semmel’s development model. This model is known as the 4-D Model (Define, Design, Develop, and Disseminate). The data were obtained through a paper’s validation product, and also an interview with the six PAI’s teachers of Elementary schools in Makassar City. This research is considered effective and valid as the reference of teaching materials in Islamic Education and Character has 80.24 of the effectiveness from the teaching materials and 3.68 values of validity.Abstrak:Penelitian ini dirancang untuk mendeskripsikan profil pengembangan bahan ajar Pendidikan Agama Islam dan Budi Pekerti berbasis nilai-nilai kearifan lokal, serta melaksanakan pengembangan bahan ajar pendidikan Agama Islam dan budi pekerti berbasis nilai-nilai kearifan lokal yang valid, praktis, dan efektif. Penelitian ini menggunakan penelitian pengembangan yang mengacu pada teori model pengembangan Thiagarajan dan Semmel. Model ini dikenal dengan Model 4-D (Define, Design, Develop, and Disseminate). Data diperoleh melalui lembar validasi produk, serta wawancara dengan enam guru SD PAI di Kota Makassar. Penelitian ini dinilai valid dan efektif sebagai referensi bahan ajar Pendidikan Agama Islam dan Budi Pekerti karena memiliki nilai keefektifan bahan ajar sebanyak 80,24 dan tingkat kevalidan sebanyak 3,68.